1) Dados A = (2x -1) e B = (2x +1) DETERMINE:
a)
- ![B^{2} B^{2}](https://tex.z-dn.net/?f=+B%5E%7B2%7D+)
b) (A - B)
Soluções para a tarefa
Respondido por
2
a) ![( 2x-1)^{2} - (2x+1)^{2} ( 2x-1)^{2} - (2x+1)^{2}](https://tex.z-dn.net/?f=%28+2x-1%29%5E%7B2%7D+-+++%282x%2B1%29%5E%7B2%7D+)
![2x^{2} -2x + 1 - (2x^{2} +2x +1) 2x^{2} -2x + 1 - (2x^{2} +2x +1)](https://tex.z-dn.net/?f=2x%5E%7B2%7D+-2x+%2B+1+-+%282x%5E%7B2%7D+%2B2x+%2B1%29+)
![2x^{2} -2x + 1 -2x^{2} -2x -1<br />-4x<br /><br />b)[tex][(2x-1-(2x+1)]^{2} 2x^{2} -2x + 1 -2x^{2} -2x -1<br />-4x<br /><br />b)[tex][(2x-1-(2x+1)]^{2}](https://tex.z-dn.net/?f=2x%5E%7B2%7D+-2x+%2B+1+-2x%5E%7B2%7D+-2x+-1%3Cbr+%2F%3E-4x%3Cbr+%2F%3E%3Cbr+%2F%3Eb%29%5Btex%5D%5B%282x-1-%282x%2B1%29%5D%5E%7B2%7D+)
= 4
Perguntas interessantes